ANALYSIS OF ATMOSPHERIC CONDITION ON HAIL EVENT AT PELALAWAN (CASE STUDY: SEPTEMBER 23RD, 2019) - Mari Frystine; Aditya Mulya; Aries Kristianto; Meldisa Putri Maulidyah (Jurnal Meteorologi dan Geofisika, 2022)
In Pulau Muda Village, hail occurred on September 23rd, 2019 when the entire Riau area was covered by smoke due to forest and land fires phenomenon. The hail was not accompanied by extreme rain and did not cause material harm. However, a study of atmospheric conditions before, during, and after hail occurred is needed to reference for the early warning of future events. The identification of hail cloud stage used the C-Band Radar Reflecticity, Himawari-8 Satellite, and Rain Gauge data. Model data processed by GrADS are used to support the analysis of meteorological parameter. The surface condition are the opposite to the previous study that the surface air temperature increases 2oC and RH decreased 10% from h-1 caused by dry air of the smoke phenomenon. The hail occurred from one single cell CB cloud that developed within 30 minutes reaching the mature stage with its maximum reflectivity core was 65 dBZ and cloud top temperature decreased to -75oC at 06.00 UTC. The convective activity with maximum updraft -1.9 Pa.s-1developed the cloud as the CAPE index increased from 150 to 700 J.kg-1 from 05.00 to 06.00 UTC. The decrease of specific ice water content with maximum downdraft 0,2 Pa.s-1 from 06.00 - 07.00 UTC evidenced that the cloud ice layer produced the hail at the mature to dissipation stage of the cloud. Further study is needed by providing chemistry model data in order to understand more about hail in tropics especially in this unique situation that is among the smoke phenomenon.